2020
DOI: 10.1101/2020.07.16.205088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single intranasal dose of chimpanzee adenovirus-vectored vaccine confers sterilizing immunity against SARS-CoV-2 infection

Abstract: SUMMARYThe Coronavirus Disease 2019 pandemic has made deployment of an effective vaccine a global health priority. We evaluated the protective activity of a chimpanzee adenovirus-vectored vaccine encoding a pre-fusion stabilized spike protein (ChAd-SARS-CoV-2-S) in challenge studies with Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and mice expressing the human angiotensin-converting enzyme 2 receptor. Intramuscular dosing of ChAd-SARS-CoV-2-S induces robust systemic humoral and cell-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…To date, six intranasal and three oral vaccine candidates are in clinical Phase 1 or 2 trials [ 2 ]. While data from clinical trials have not yet been published, preclinical studies suggest the induction of mucosal immunity [ 69 ]. First results from clinical trials of an oral vaccine candidate by Vaxart Inc. have recently been announced [ 70 ].…”
Section: Immune Response To Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…To date, six intranasal and three oral vaccine candidates are in clinical Phase 1 or 2 trials [ 2 ]. While data from clinical trials have not yet been published, preclinical studies suggest the induction of mucosal immunity [ 69 ]. First results from clinical trials of an oral vaccine candidate by Vaxart Inc. have recently been announced [ 70 ].…”
Section: Immune Response To Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…Whether or not strong immune responses to the S protein alone will provide adequate protection is still unclear, but the limited evidence from the animal challenge studies previously discussed seem to indicate that this may be sufficient to protect against severe disease. More recently, trials deploying intranasal immunisation using the S protein have been shown to elicit a broad spectrum of antibodies and T cell responses, including local mucosal responses, which may be a promising avenue for improving vaccine efficacy ( 163 ).…”
Section: Discussionmentioning
confidence: 99%
“…This route of administration may fail to generate a protective immune response in the upper respiratory tract that would otherwise be generated in natural infection ( 98 ). Hassan et al demonstrated that a single-dose of intranasal administration of a ChAd-vectored S vaccine induced a local immune response that was sufficient to provide sterilising immunity in mice ( 163 ). There is reason to believe that local immunisation with a vaccine that can generate an IgA mucosal antibody response in the upper respiratory tract may provide a robust strategy for effective early clearance, as shown in successful trials of measles and BCG vaccines administered through the aerosol route ( 164 , 165 ).…”
Section: Vaccine-induced Immunitymentioning
confidence: 99%
“…We saw stronger serum IgG and NAb titers in our study compared to a ChAdOx1-nCov in Balb/c mice 4 , however, this might reflect differences in assay components. A rAd36 vaccine study was performed by Hassan, et al, where doses of 1e10 VP were given by intranasal delivery 49 . The results were significant from the standpoint of blocking lung infection in a mouse SARS-CoV-2 challenge model.…”
Section: Discussionmentioning
confidence: 99%